Soucasné Flámske Umeni. - Elias, Willem (Praha : Galerie Art Centrum, 1976)
Bauters, Sonja Rosalia ; Bilquin, Jean ; Brems, Walter ; Burssens, Jan ; Cleremans, Raf ; De Bruyne, Gustaaf C. ; De Coster, Jean Pierre ; De Kramer, Enk ; D'Havé, Camille ; De Winter, Roland ; Everaert, Felix ; Goris, An ; Haerden, Boy ; Landuyt, Octave ; Muller, Koen ; Raveel, Roger ; Roobjee, Pjeroo ; Van Bruaene, Jackie ; Van Den Abbeel, Jan ; Van Den Dries, Maurice ; Veris, Renat ; Vlerick, Pierre ; Wittevrongel, Roger
Soucasné Flámske Umeni, Galerie Art Centrum, Praha, 3-30 kvetna 1976
boek
Keywords: Vlaanderen; België